USP22 controls type III interferon signaling and SARS-CoV-2 infection through activation of STING - Karlowitz, Rebekka; Stanifer, Megan; Roedig, Jens; Andrieux, Geoffroy; Bojkova, Denisa; Bechtel, Marco; Smith, Sonja; Kowald, Lisa; Schubert, Ralf; Börries, Melanie; Cinatl, Jindrich; Boulant, Steeve; et al. (Cell death & disease, 2022)
Pattern recognition receptors (PRRs) and interferons (IFNs) serve as essential antiviral defense against SARS-CoV-2, the causative agent of the COVID-19 pandemic. Type III IFNs (IFN-λ) exhibit cell-type specific and long-lasting functions in auto-inflammation, tumorigenesis, and antiviral defense. Here, we identify the deubiquitinating enzyme USP22 as central regulator of basal IFN-λ secretion and SARS-CoV-2 infections in human intestinal epithelial cells (hIECs). USP22-deficient hIECs strongly upregulate genes involved in IFN signaling and viral defense, including numerous IFN-stimulated genes (ISGs), with increased secretion of IFN-λ and enhanced STAT1 signaling, even in the absence of exogenous IFNs or viral infection. Interestingly, USP22 controls basal and 2′3′-cGAMP-induced STING activation and loss of STING reversed STAT activation and ISG and IFN-λ expression. Intriguingly, USP22-deficient hIECs are protected against SARS-CoV-2 infection, viral replication, and the formation of de novo infectious particles, in a STING-dependent manner. These findings reveal USP22 as central host regulator of STING and type III IFN signaling, with important implications for SARS-CoV-2 infection and antiviral defense.
Gesehen am 13.03.2023